CONCORDANCE BETWEEN OBJECTIVE AND SUBJECTIVE MEASURES OF COGNITIVE FUNCTION. (11th November 2018) - Sidlowski, S; Drury, J; Leonard, B; Mostowy, M; Perls, T; Andersen, S
Abstract: Introduction: Studies use multiple measures of cognitive function to assess for dementia. By examining concordance between objective and subjective questionnaires, we can gain insight into the benefits and drawbacks of these measures. Methods: New England Centenarian Study offspring participants (N=599, mean age 83.3+/-7.0 years) completed objective cognitive assessments (Telephone Interview for Cognitive Status, TICS-m) and informants completed the Dementia Questionnaire (DQ) which inquires about symptoms of cognitive and functional impairments. Dementia was indicated by a TICS-m score <27 (TICS+) or impairments in both memory and ADLs on the DQ (DQ+). Results: 44 offspring were TICS+ of which 55% (n=24) were also DQ+. Discordance was due to false-positive deflation of TICS scores from sensorimotor impairments, poor informant reliability/bias on the DQ, and the requirement of an ADL impairment for DQ+. For 62 who were DQ+, 39% (n=24) were TICS+. Discordance for DQ+ participants were due to overstatement of memory impairment by informants. Of the 555 who were TICS-, 93% were DQ-. Conclusion: Inherently, with questions that measure specific cognitive functions, the TICS is less prone to administrator bias. The DQ, however, is more ecologically valid; it is able to pick up on impairment in everyday life that cannot be detected by formal test questions; an advantage that is countered in part by informant bias. High concordance for negative dementia status suggests that either measure is sufficient for ruling out dementia whereas the lower concordance for positive dementia status indicates there is greater sensitivity by using the two together to detect dementia.